Impact of clinical pharmacist interventions on medication administration via enteral feeding tubes in a neurology ward: a pre- and post-educational prospective study - Ayhan, Yunus Emre; Özkanlı, Ömer Faruk; Gözelizmir, Şeyma; Al-Taie, Anmar; Sancar, Mesut; Midi, Ipek (Frontiers in Pharmacology, 2025)
ObjectivesThe aim of this study was to evaluate the effects of clinical pharmacists’ education and interventions on the appropriateness of dosage forms of drugs administered via the enteral feeding tubes (EFTs) in hospitalised patients in the neurology ward.MethodsThis was a prospective, pre-post intervention study conducted among patients and neurologist team professionals in the neurology ward of a training and research hospital in Istanbul, Türkiye. The study was designed in two phases as a pre-education observation period (OP) and a post-education intervention period (IP), during which the clinical pharmacists provided the required recommendations. Medications evaluated in terms of EFT-related medication administration errors (EFTRMAE) during the hospitalisation and discharge of patients in OP and IP. The knowledge levels of the neurologist team regarding EFT medication administration were collected and evaluated with an online survey before and after the education program.ResultsA total of 68 patients were included in the study, with 34 patients in the OP and 34 in the IP. During hospitalisation, EFTRMAEs were observed in 24 patients (70.6%) in the OP, whereas in the IP, EFTRMAEs were detected in 13 patients (38.2%) before clinical pharmacist interventions (p = 0.014). Throughout hospitalisation in the IP group, clinical pharmacists provided 25 interventions related to EFTRMAEs, of which 84% were accepted by physicians. However, only 11 of the accepted recommendations were fully implemented. Following these interventions, inappropriate drug administration via EFT remained in only 5 patients (14.7%) (p < 0.001). At hospital discharge, the EFTRMAE rate, which was 76.5% in the OP group, decreased to 23.5% in the IP group (p < 0.001). The neurologist team’s knowledge of EFT medication administration improved significantly following clinical pharmacist education, with the average number of correct responses increasing from 16.1 ± 4 before the education to 21.1 ± 2.1 afterward (p < 0.001).ConclusionEFTRMAEs are frequently encountered in patients hospitalised in the neurology ward. Including clinical pharmacists in the healthcare team and the education program provided to physicians and nurses will increase the knowledge level of participants and the ability of physicians to prescribe appropriate dosage forms for administration via EFT.